2021
DOI: 10.1021/acs.langmuir.1c01801
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Acceptor Pairs in Covalent Organic Frameworks Promoting Electron Transfer for Metal-Free Photocatalytic Organic Synthesis

Abstract: The donor−acceptor-type covalent organic frameworks (COFs) have recently gained increasing interest in photocatalysis, but the photoinduced electron-transfer regimes in the COFs are underexplored. Herein, we demonstrate a designed porphyrinic COF possessing a donor− acceptor structure together with its photocatalytic performance in aerobic coupling of primary amines. The COF could be photoexcited by the full range of visible light to generate electron−hole pairs that could be separated by donor−acceptor pairs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…The result (Figure 7a, ZnAgInS/COF(5) + Always dark) showed that there was no obvious dye degradation under the dark condition. As shown in Figure 7a, the absorption efficiencies of the samples for RhB after 30 min of dark reaction were 3.6, 3.8, 3.2, 4.6, 4, and 3.6% for ZnAgInS, COF, ZnAgInS/ COF(2.5), ZnAgInS/COF(5), ZnAgInS/COF (15), and ZnA-gInS/COF (25), respectively. This indicates that the absorption capacities of the prepared samples are close and without obvious differences.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The result (Figure 7a, ZnAgInS/COF(5) + Always dark) showed that there was no obvious dye degradation under the dark condition. As shown in Figure 7a, the absorption efficiencies of the samples for RhB after 30 min of dark reaction were 3.6, 3.8, 3.2, 4.6, 4, and 3.6% for ZnAgInS, COF, ZnAgInS/ COF(2.5), ZnAgInS/COF(5), ZnAgInS/COF (15), and ZnA-gInS/COF (25), respectively. This indicates that the absorption capacities of the prepared samples are close and without obvious differences.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…As shown in Scheme 1, the ZnAgInS/COF was prepared with a facile oil bath heating method that was similar to the preparation of ZnAgInS, except for the addition of TpPa-1 COF at the first step. The prepared ZnAgInS/COF composites with different amounts of TpPa-1 COF (2.5, 5, 15, and 25 wt %) were denoted as ZnAgInS/COF(2.5), ZnAgInS/COF(5), ZnAgInS/COF (15), and ZnAgInS/COF (25), respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Their tailorable chemical structure allows for tuning of the electronic state of encapsulated metal NPs by tuning the interactions between the pore wall atoms and metal atoms. 27 Importantly, each atom in the framework can be precisely determined, 28–30 which is key to studying the detailed catalytic mechanism and structure–activity relationships. All these factors make COFs promising candidates to encapsulate metal NPs, 31 particularly small metal NPs.…”
Section: Introductionmentioning
confidence: 99%